Dialog Sufistik: Membangun Relasi antar-Agama yang Konstruktif - Gumilar Irfanullah; Hasse J Hasse J (ILMU USHULUDDIN, 2016)
This writing is a proposal of a dialogue model for interreligious interests, in which it stresses on communication without neglecting a faith of each religion, and at the same time it does not leave the faith itself. It is a Sufis dialog, which no longer views that some beleiver’s faith is not flexible, but it is seen as a means to build an open communication, in which thence it can create a format of dialog which contributes enhancement and goodness for living together in between human beings. Therefore, this article also offers a dialogue methodology, which is the most ideal, i.e. spiritual dialog which bestows universal Sufis values that embrace all kinds of beliefs and faiths.